2022
DOI: 10.3390/ani12060771
|View full text |Cite
|
Sign up to set email alerts
|

Invited Review: Antimicrobial Use and Antimicrobial Resistance in Pathogens Associated with Diarrhea and Pneumonia in Dairy Calves

Abstract: Antimicrobial use (AMU) is the major driver of antimicrobial resistance (AMR) among bacteria in dairy herds. There have been numerous studies on AMU and AMR in dairy cows; however, studies on AMU and AMR in dairy calves are limited. A comprehensive overview of the current state of knowledge of AMU and AMR among pathogens in dairy calves is important for the development of scientifically supported and applicable measures to curb antimicrobial use and the increasing risk of AMR. Therefore, we performed a systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 98 publications
0
2
1
Order By: Relevance
“…Predominant respiratory pathogens causing death in animals from 2 months to 1 year old were P. multocida , M. haemolytica , and T. pyogenes . Pasteurella multocida and M. haemolytica have been cited as the most common causes of pneumonia including fatal cases in this age group [ 30 , 31 ], but T. pyogenes was diagnosed as the primary cause of death in the present study more frequently than some reports. However, a literature review found the latter to be an important respiratory pathogen in dairy cattle as well [ 32 ].…”
Section: Discussioncontrasting
confidence: 67%
“…Predominant respiratory pathogens causing death in animals from 2 months to 1 year old were P. multocida , M. haemolytica , and T. pyogenes . Pasteurella multocida and M. haemolytica have been cited as the most common causes of pneumonia including fatal cases in this age group [ 30 , 31 ], but T. pyogenes was diagnosed as the primary cause of death in the present study more frequently than some reports. However, a literature review found the latter to be an important respiratory pathogen in dairy cattle as well [ 32 ].…”
Section: Discussioncontrasting
confidence: 67%
“…Though various kinds of measures have been implemented so far to fight against diarrhea, there is still a long way to go ( Cho et al, 2013 ). A recent review found that higher antimicrobial resistance was associated with the drugs being used for the treatment of diarrhea ( Zhang H. et al, 2022 ; Zhang X. et al, 2022 ); therefore, establishing a method to positively regulate the gut microbiota to ameliorate diarrhea is of great importance and meaningful ( Coelho et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Weaned dairy heifers represent a unique production group, compared to pre-weaned calves or adult cattle, in which to study BRD and AMR. This population has unique management conditions that may influence BRD and AMR; they have recently been weaned off milk feeding, which is stressful [ 4 , 5 ], and many have received prior treatment with AMD during the pre-weaned period for BRD or diarrhea [ 3 , 6 , 7 , 8 , 9 , 10 ], and have been moved to group housing where they may be comingled with calves from other farms, which represents stress and a risk for pathogen and AMR spread [ 3 , 11 ]. Antimicrobial resistance (AMR) in food animals is an animal health, welfare, and One Health concern [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%